Traditional dye yielding plants of Tripura, Northeast India - BISWAJIT SUTRADHAR; DIPANKAR DEB; KOUSHIK MAJUMDAR; B K DATTA (Biodiversitas Journal of Biological Diversity, 2015)
Sutradhar B, Deb D, Majumdar K, Datta BK. 2015. Traditional dye yielding plants of Tripura, Northeast India. Biodiversitas 16: 121-127. This present paper deals with the survey of traditional dye yielding plants, their ethnobotanical usage and cultural practices by the different ethnic communities of Tripura. Field investigation was carried out in different villages and adjacent forest pockets in South and West district of the State. The ethnobotanical information was collected based on semi-structured questioner, personal interviews and group discussion among the major ethnic communities of Tripura. The study reports a checklist of 39 species of dye yielding plants belonging to 35 genera and 26 families documented along with their vernacular name, habit, parts use. The active coloring agents were also listed for each plant based on earlier reports. Natural dye yielding plants have immense significance in the socio-economic and socio-cultural life of indigenous ethnic people and if we promote these products in a managed way then efforts towards preservation of traditional knowledge and local biodiversity will be more fruitfully achieved. Keywords: Dye yielding plants, indigenous knowledge, natural products, Tripura